2008
DOI: 10.1111/j.1365-2427.2008.02059.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of land use on stream ecosystem function in a Mediterranean catchment

Abstract: 1. Due to the hierarchical organization of stream networks, land use changes occurring at larger spatial scales (i.e. the catchment) can affect physical, chemical and biological characteristics at lower spatial scales, ultimately altering stream structure and function. Anthropogenic effects on streams have primarily been documented using structural metrics such as water chemistry, channel alteration and algal biomass. Functional parameters, including metrics of nutrient retention and metabolism, are now being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
83
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 63 publications
(125 reference statements)
5
83
1
Order By: Relevance
“…Consequently, cities or villages intensity has increased over these ten years, particularly in the upper and lower reaches of the stream. As we know, this extensive and ever-increasing urbanization leads to a threat to stream ecosystem [18]. The results confirmed our prediction that urban land was the primary factor to explain the deterioration of water quality.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Consequently, cities or villages intensity has increased over these ten years, particularly in the upper and lower reaches of the stream. As we know, this extensive and ever-increasing urbanization leads to a threat to stream ecosystem [18]. The results confirmed our prediction that urban land was the primary factor to explain the deterioration of water quality.…”
Section: Discussionsupporting
confidence: 88%
“…Statistic analysis. Sites were subjectively split into three groups: (1) headwater (sites 1-8); (2) mid-reach (sites 9-15); and (3) lower reaches (sites [16][17][18][19][20]. Differences between sites were compared with a parameteric analysis of variance (ANOVA) and significant differences were accepted at P < 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have shown that inorganic N uptake decreases with increasing developed land use as a result of higher stream inorganic N concentrations reducing biotic demand for uptake (Niyogi et al 2004;Von Schiller et al 2008). However, this effect can be offset, or exceeded, by higher resource availability in developed land use streams increasing biotic biomass and metabolism, and thus increasing nutrient demand (Hall et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Rivers and riparian areas of Iberia, Southwestern Europe, have been subjected to huge human disturbances for millennia, such as water diversion, regulation, land-use, afforestation, grazing, physical interventions on riverbanks, amongst others Hooke, 2006;von Schiller et al, 2008). These manifold types of pressures often result in biodiversity and habitat loss, and invasion by alien plant species, as well as an overall degradation of the riparian ecosystem (Aguiar et al, 2001;Allan, 2004;Aguiar and Ferreira, 2005).…”
Section: Introductionmentioning
confidence: 99%